Cover Image. (8th March 2020) - Wu, Yiling; Shao, Xiaoqing; Jiao, Hang; Song, Xinwei; He, Kun; Li, Zhen
Abstract : The cover image is based on the Research Article Tracking the fungus‐assisted biocorrosion of lead metal by Raman imaging and scanning electron microscopy technique by Yiling Wu et al., https://doi.org/10.1002/jrs.5796 .